Eclogite from the Pohorje Mountains - Hinterlechner-Ravnik, Ana (Geologija, 1982)
In the polymetamorphic terrains of the Pohorje Mountains eclogite is encountered as small lenses usually boudin shaped in almandine-muscovite schist. Eclogite is associated with amphibolite and serpentinite. The largest assemblage of these rocks occurs at Slovenska Bistrica along a deep fault which may be related to the prominent Periadriatic lineament. The serpentinite body extends for five kilometers. The amphibolite band is still larger and the eclogitic lens does not exceed one kilometer. Eclogite and its mineral phases were analysed optically and chemically. Some conclusions about the crystallization of eclogite and its surrounding rocks are given.